1996
DOI: 10.1021/ja952998h
|View full text |Cite
|
Sign up to set email alerts
|

Novel Keto−Enol Systems:  Cyclobutane Derivatives

Abstract: 3H-Perfluorobicyclo[2.2.0]hexan-2-one (3) has been synthesized from hexafluorobenzene and equilibrated with its enol form (4). In carbon tetrachloride K e/k = 0.07 ± 0.01 (25 °C), but in Lewis basic solvents (e.g. acetonitrile, ether, and tetrahydrofuran) only enol is detectable at equilibrium because of its strength as a hydrogen bond donor. In the monocyclic counterpart of this keto−enol system, 2H-perfluorocyclobutanone (1) and perfluorocyclobut-1-enol (2), the enol is more stable yet. Here ketone is undete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
7
19
0
Order By: Relevance
“…Thus the difference in the heat of formation is reduced to 2.319 kcal/mol as compared to the parent (without perfluorination, 10.638 kcal/mol). Therefore the perfluorination process causes a destabilisation of the ketone and a stabilisation of the enol, which agrees with the work of Lindner et al [14] and with the large basis set of B3LYP [15]. This is supported by calculation of the Gibbs free energy (∆G), which is found to be 1.639 kcal/mol and less than that of the parent (without fluorination, 7.792 kcal/mol).…”
Section: Parent Cyclobutanone and Its Enol Counterpart With Perfluorisupporting
confidence: 90%
See 3 more Smart Citations
“…Thus the difference in the heat of formation is reduced to 2.319 kcal/mol as compared to the parent (without perfluorination, 10.638 kcal/mol). Therefore the perfluorination process causes a destabilisation of the ketone and a stabilisation of the enol, which agrees with the work of Lindner et al [14] and with the large basis set of B3LYP [15]. This is supported by calculation of the Gibbs free energy (∆G), which is found to be 1.639 kcal/mol and less than that of the parent (without fluorination, 7.792 kcal/mol).…”
Section: Parent Cyclobutanone and Its Enol Counterpart With Perfluorisupporting
confidence: 90%
“…But the order of stability reverses at a larger basis set, that is, B3LYP/6-311++G * * //B3LYP/6-31+G * at which enol becomes ∼ 1.0 kcal/mol more stable than ketone. This fact agrees with the thermodynamic equilibrium constant between ketone and enol [14]. In the case of 2,2H-Perfluorocyclobutanone it was found that the ketone is more stable than its enol counterpart [15].…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…(6)). Protonation of the resulting enolate (33) gave the enol (34) [21], which we found some years ago to be lower in energy than its keto form [22]. Under our conditions, perfluorocyclohexane (30) was reduced very slowly if at all even by potassium benzophenone ketyl.…”
Section: Functionalization Without Lightmentioning
confidence: 67%